Image Processing, Analysis and Machine Vision - Boyle Roger; Hlavac Vaclav; Sonka Milan (Chapman & Hall Computing, 1995)
Digital Image Analysis, Machine Vision and Intelligent Robotics. Preface, Introduction, The Digitized Image and Its Properties, Data Structures for Image Analysis, Image Pre-Processing, Segmentation, Shape Representation and Description, Object Recognition, Image Understanding, 3D Vision, Mathematical Morphology, Linear Discrete Image Transforms, Image Data Compression, Texture, Motion Analysis, Index.